1993
DOI: 10.1111/j.1365-2605.1993.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific antigen and prostate gland size in men receiving exogenous testosterone for male contraception

Abstract: Steroid regimens containing androgens are being evaluated currently as hormonal contraceptives for men. The possible non-reproductive effects of such treatment were assessed during an efficacy trial using a prototype regime of 200 mg testosterone enanthate i.m. weekly. Prostatic function and size were monitored by regular rectal examination, blood levels of prostate-specific androgen (PSA) were measured in 30 men and prostatic size was measured by trans-rectal ultrasound imaging in a representative subgroup of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 23 publications
(28 reference statements)
2
10
0
2
Order By: Relevance
“…Our results suggest that PSA levels could not be used as an index of androgen action in the treatment of male hypogonadism since its level was correlated with only in a subgroup of male hypogonadism after treatment. Wallace et al [20], supporting this view, reported that supraphysiological serum testosterone levels after high-hose testosterone enanthate administration in healthy subjects did not result in changes in serum PSA levels. Although Behre et al [11] …”
Section: Discussionsupporting
confidence: 52%
“…Our results suggest that PSA levels could not be used as an index of androgen action in the treatment of male hypogonadism since its level was correlated with only in a subgroup of male hypogonadism after treatment. Wallace et al [20], supporting this view, reported that supraphysiological serum testosterone levels after high-hose testosterone enanthate administration in healthy subjects did not result in changes in serum PSA levels. Although Behre et al [11] …”
Section: Discussionsupporting
confidence: 52%
“…Effective testosterone substitution therapy of hypogonadal men increases prostate volume to a level comparable to that of age-matched normal males [3,12]. For male contraception, highdose administration of testosterone enanthate to normal men, leading to continuously supraphysiological level of serum testosterone, did not result in changes of serum PSA levels, although a minor increase in prostate volume was observed [15]. In the present study, too, testosterone replacement therapy caused no change in serum PSA but a significant increase in prostate volume in Klinefelter syndrome.…”
Section: Discussionmentioning
confidence: 92%
“…The present study is the first report recording changes in prostate structure and secretory activity in a primate injected exogenously with TE for more than 2 years. Previously, Wallace et al (1993) reported a small but significant increase in maximal prostate transverse area in four men who participated in the efficacy trial using 200 mg TE injected weekly for 1 year. The marked increase in PAP levels in treated animals suggests that TE injections have promoted the secretory activity of prostate epithelial cells.…”
Section: Discussionmentioning
confidence: 98%